Major Constituents of Cannabis Vape Oil Liquid, Vapor and Aerosol in California Vape Oil Cartridge Samples - Guo, Weihong; Vrdoljak, Gordon; Liao, Ven-Chi; Moezzi, Bahman (Frontiers in Chemistry, 2021)
During the E-cigarette or Vaping product use Associated Lung Injury (EVALI) outbreak of August 2019 to February 2020, the California Department of Public Health, Food and Drug Laboratory Branch received numerous cannabis vape oil cartridge investigation samples from throughout the state. Many of these products were directly linked to patients; others were collected as part of investigations. We determined the major ingredients and additives in twelve unused cannabis vape oil cartridge samples obtained before (n = 2) and during the EVALI outbreak (n = 10) in California from September 2018 to December 2019. We tested for major constituents in vape oil liquid, vape oil vapor, and vape oil aerosol phases. A nontargeted Gas Chromatography Mass Spectrometry direct injection screening method was developed for vape oils, a headspace heating module used for vape oil vapors and a solid-phase microextraction (SPME) vaping rig for aerosols generated by vaping. We have identified more than 100 terpenes and natural extracts, 19 cannabinoids, and other potential toxic additives such as Vitamin E Acetate, Polyethylene Glycols, and Medium Chain Triglycerides. We determined more terpenes and minor cannabinoids can be produced via vaporizing and aerosolizing the vape oil. Delta9-THC and potential toxic additives were found at lower levels in the vapor and aerosol than in the vape liquid.